1996
DOI: 10.1007/s002560050146
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in chronic achilles tendinopathy: a comparison of ultrasonography, magnetic resonance imaging and surgical findings in 27 histologically verified cases

Abstract: Surgical findings included 4 partial ruptures, 21 degenerative lesions and 2 macroscopically normal cases. Microscopy revealed tendinosis (degeneration) in all tendon biopsies, including cases with a partial rupture, but only slight changes in the paratendinous tissues (paratenon). Ultrasonography was positive in 21 of 26 and MRI in 26 of 27 cases. Severe intratendinous abnormalities and a sagittal tendon diameter > 10 mm suggested a partial rupture. In tendons with a false negative result histopathological ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
90
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(96 citation statements)
references
References 21 publications
1
90
0
3
Order By: Relevance
“…Imaging is useful for documenting tendon changes, as well as ruling out other causes of patients' symptoms (Shalabi et al, 2001, Kader et al, 2002, Paavola et al, 2002a, Shalabi et al, 2004b, Shalabi et al, 2004c, Bleakney and White, 2005 US is a quick, safe and inexpensive method, but it is regarded as very user dependent and requires an experienced radiologist (Sandmeier and Renström, 1997). US is valuable for finding the occurrence and location of tendon lesions, but it is unable to differentiate between partial tendon ruptures and focal degenerative areas (Åström et al, 1996(Åström et al, , Paavola et al, 1998. Sometimes mild to moderate changes can be found in both symptomatic and asymptomatic tendons and the changes that are seen are not always related to patients' symptoms (Paavola et al, 1998, Fredberg and Bolvig, 2002, Peers et al, 2003b.…”
Section: Imaging Methodsmentioning
confidence: 99%
“…Imaging is useful for documenting tendon changes, as well as ruling out other causes of patients' symptoms (Shalabi et al, 2001, Kader et al, 2002, Paavola et al, 2002a, Shalabi et al, 2004b, Shalabi et al, 2004c, Bleakney and White, 2005 US is a quick, safe and inexpensive method, but it is regarded as very user dependent and requires an experienced radiologist (Sandmeier and Renström, 1997). US is valuable for finding the occurrence and location of tendon lesions, but it is unable to differentiate between partial tendon ruptures and focal degenerative areas (Åström et al, 1996(Åström et al, , Paavola et al, 1998. Sometimes mild to moderate changes can be found in both symptomatic and asymptomatic tendons and the changes that are seen are not always related to patients' symptoms (Paavola et al, 1998, Fredberg and Bolvig, 2002, Peers et al, 2003b.…”
Section: Imaging Methodsmentioning
confidence: 99%
“…Although both imaging techniques can locate lesions, they cannot differentiate between tendinosis and partial rupture. 5 Also, pathological findings correlate poorly with patient symptoms. 23 Khan et al 17 suggested that imaging may offer little additional information to experienced clinicians.…”
Section: Limitationsmentioning
confidence: 99%
“…However, MRI has a clear advantage over US, as the images more easily can be evaluated in a standardized manner in longitudinal studies (Movin, PhD thesis, 1998). The literature suggests that MRI and US are superior to other imaging modalities in the detection and evaluation of intratendinous changes (Åström et al, 1996(Åström et al, , Movin et al, 1998. MR imaging can provide important information about the pathologic state of the Achilles tendon, and these imaging findings can provide information that is useful in patient treatment (Schweizer and Karasick, 2000).…”
Section: Mrimentioning
confidence: 99%